KONFLIK PERAN DAN KELELAHAN EMOSIONAL PENGARUHNYA TERHADAP KINERJA DOSEN PADA UNIVERSITAS MAJALENGKA - Dadang Sudirno (MAKSI, 2015)
This research to know examine of role conflict, emotional exhaustion andperformance of Univesitas Majalengka lecturer. To know the influence of role conflict andemotional exhaustion on the performance of Universitas Majalengka lecturer.The research method used in this research is descriptive analysis techniques andverification. Samples at this research that proportional random sampling. Data collectingtechniques that is with questionnaire. Testing of instrument of data is done with validitytest and reliability test, while data analysis applied is correlation, determination,regression and hypothesis test.Based on result of research for role conflict and emotional exhaustion ofUniversitas Majalengka lecturer is included in low category, and for the performance oflecturer is included in high category. Relation between role conflict with not concurrentperformance of lecturer (negatif valuable) that coleration is including medium category.Relation between emotional echaustion with not concurrent performance of lecturer(negatif valuable) that coleration is including low category. Relation together between roleconflict and emotional exhaustion with not concurrent performance of lecturer (negatifvaluable) that coleration is including medium category.Keyword: role conflict, emotional exhaustion and performance of lecturer